SUPERBLOK BISNIS DENGAN PENDEKATAN GREEN METROPOLIS DI JAKARTA UTARA, PENEKANAN PADA AREA BISNIS DAN KOMERSIAL - Galih Ajie Nugraha; B. Heru Santosa; Amin Sumadyo (ARSITEKTURA, 2015)
Business Superblock in North Jakarta motivated by the potential and high economic attractiveness of Jakarta but not matched with good urban planning so that Jakarta is not ready to accept urbanization and has residential and transportation issues. The objective of this scheme is to get the design of superblock area is able to accommodate business and commercial activities, supported by residential facilities and access to public transportation. The method used is a method of planning and architectural design through an approach that is taken from the book of David Owen: Green Metropolis : Why Living Smaller, Living Closer, and Driving Less are the keys to sustainability. Design issues to be resolved are: the selection and processing footprint suitable for the needs of a superblock, and can support both business and commercial activity as main activity, as well as residential and recreational activities as secondary activities. The results are a design of superblock area is able to accommodate business activities and commercial (work), residential, and recreation with the support of public transportation access with the Green Metropolis approach. Keywords: Business Superblock, Green Metropolis, Business and Commercial, Mix-Used.